2017
DOI: 10.1002/cctc.201700916
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Acidity in Bulk and Nanosheet [T]MFI (T=Al3+, Ga3+, Fe3+, B3+) Zeolites in the Methanol‐to‐Hydrocarbons Reaction

Abstract: The influence of framework substituents (Al3+, Ga3+, Fe3+ and B3+) and morphology (bulk vs. nanometer‐sized sheets) of MFI zeolites on the acidity and catalytic performance in the methanol‐to‐hydrocarbons (MTH) reaction was investigated. The Brønsted acid density and strength decreased in the order Al(OH)Si>Ga(OH)Si>Fe(OH)Si≫B(OH)Si. Pyridine 15N NMR spectra confirmed the differences in the Brønsted and Lewis acid strengths but also provided evidence for site heterogeneity in the Brønsted acid sites. Owing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 88 publications
(122 reference statements)
1
26
0
Order By: Relevance
“…The quantitative analysis for fractions of extra-framework Al in these 2D MFI zeolites has been done by comparing the peak area of each species visible in the 27 Al MAS NMR spectra. As shown in Table 11, multilamellar MFI contains more extra-framework Al than pillared MFI, while the 3D MFI has much less extra-framework Al compared to these two derivatives [245,249]. Overall, the fraction of extra-framework Al is indicative of the defective nature of 2D MFI zeolites, which is expected to follow the order of unilamellar MFI > multilamellar MFI > pillared MFI > 3D MFI.…”
Section: Acidity Characterization For 2d Mfi Zeolitesmentioning
confidence: 96%
See 4 more Smart Citations
“…The quantitative analysis for fractions of extra-framework Al in these 2D MFI zeolites has been done by comparing the peak area of each species visible in the 27 Al MAS NMR spectra. As shown in Table 11, multilamellar MFI contains more extra-framework Al than pillared MFI, while the 3D MFI has much less extra-framework Al compared to these two derivatives [245,249]. Overall, the fraction of extra-framework Al is indicative of the defective nature of 2D MFI zeolites, which is expected to follow the order of unilamellar MFI > multilamellar MFI > pillared MFI > 3D MFI.…”
Section: Acidity Characterization For 2d Mfi Zeolitesmentioning
confidence: 96%
“…The results have shown that, in randomly stacked (i.e., unilamellar) MFI nanosheets, the Al element is found not only in tetrahedral environments but also in octahedral and penta-coordinated/distorted four-coordinated positions [246]. Multilamellar MFI and its pillared form contain tetrahedral framework Al and a small amount of extra-framework Al species [48,245,248,249]. The quantitative analysis for fractions of extra-framework Al in these 2D MFI zeolites has been done by comparing the peak area of each species visible in the 27 Al MAS NMR spectra.…”
Section: Acidity Characterization For 2d Mfi Zeolitesmentioning
confidence: 99%
See 3 more Smart Citations